Caracterização do biodiesel com base na técnica de espectroscopia Raman - Alisson Marques de Miranda (2014)
Currently, the scientific community is working to create alternative energy resources through new technologies, particularly emphasizing the biofuels. Much has been done in recent years for the certification of bioethanol and biodiesel. Biodiesel is distinguished as being a clean, biodegradable, non-toxic and renewable fuel, consisting of a mixture of monoalkyl esters derived mainly from the transesterification and hydro esterification of vegetable oils, animal fats or recycled oils. Biodiesel is composed of a mixture of several esters, which can be methyl or ethyl, saturated or unsaturated. This work provides a systematic and comprehensible lineshape analysis of the Raman spectra from (i) the main esters that compose the soybean biodiesel, namely Palmitate, Stearate, Oleate, Linoleate and Linolenate, (ii) mixtures of these esters, (iii) a soybean biodiesel reference material. Using theoretical spectral simulation as a guide, the experimental spectra are fit considering all the 3N-6 vibrational modes, where N is the number of atoms in the molecules. We demonstrate that while intensity analysis may lead to uncertainty in the definition of the relative ester contents in a mixture, a complete spectral analysis involving all parameters, including peak frequencies, allows spectral determination of esters composition. Finally we defined a protocol that can be used to define the specific composition of unknown, including adulterated biodiesels, important for quality control.